Rancang Bangun Web Portal Publikasi Event Organisasi Mahasiswa Universitas Negeri Gorontalo - Saharuddin, Muhammad Dian Rezky; Dai, Roviana H; Polin, Muchlis (Gorontalo State University, 2024)
Event publications by student organizations at Universitas Negeri Gorontalo are currently conducted by posting activity posters or banners in certain areas. Additionally, event information is disseminated through personal social media pages followed by students, such as on Facebook and Instagram pages of student organizations. This approach may not ensure that all students or intended targets receive the information, as not every student or target may be aware of or follow the student organization social media accounts. Futhermore, students might not see the event posters displayed in limited campus areas. The absence of a centralized information hub containing all events to be held at Universitas Negeri Gorontalo means student spend more time checking each publication medium used by student organizations to convey information. This study aimed to develop a web portal for publishing student organizations events at Universitas Negeri Gorontalo. The study was conducted using the prototype method. The development of this web portal is expected to facilitate information dissemination by student organizations within the Universitas Negeri Gorontalo.